HUBUNGAN KECUKUPAN GIZI TERHADAP TUMBUH KEMBANG ANAK USIA PRA SEKOLAH DI DESA BONEA TIMUR WILAYAH KERJA PUSKESMAS BARUGAIA KECAMATAN BONTOMANAI KABUPATEN KEPULAUAN SELAYAR - Wilda Rezki Pratiwi; Idha Utami; St Hasriani (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2023)
Nutrition is a very important factor for growth and development. Balanced nutrition needs to be a concern for every parent, especially mothers because if the nutrition that enters the child's body is not balanced, it will cause various health problems. therefore researchers are interested in conducting research on the relationship of nutritional adequacy to growth and development in preschool-aged children. This research is a type of associative quantitative research using a correlational design. This study aims to determine whether there is a relationship between the variables studied, namely the relationship between the child's nutritional adequacy variable on the growth and development of children at preschool age in Bonea Timur Village, Bontomanai District, Selayar Islands Regency and then tested using the Chi Square Test. The results showed that for 30 respondents aged 48-72 months, the value of X2 count =26.16 ≥ X2 table 18.31 which means that there is a relationship between nutritional adequacy and growth and development in preschool-aged children in East Bonea Village, Bontomanai District. Keywords: Adequacy of Nutrition, Growth and Development, Pre-School Age Children